Simulação de cenários: planejamento estratégico do processo sucessório de um grupo empresarial - Lionço, Andréia (2017)
This research’s goal was to investigate the existing challenges of the succession process of a family corporate group, aiming to develop strategies regarding the succession process through scenarios simulation. For this purpose, the Rojo’s Model for Scenarios Simulation was applied in all its five levels: Delphi technique, competitive intelligence, scenarios simulation, strategy formulation and action plans elaboration. The research applied a qualitative approach, consisting of an exploratory study, characterized as a case study. In order to achieve the critical variables which were necessary to feed the model, the Delphi technique was applied through semi structured interviews with five experts. In the aftermath of the critical variables’ choice and the application of the competitive intelligence tools, two different scenarios were simulated. For the first scenario four strategies were formulated, and for the second scenario, other three strategies were elaborated. After that, distinct goals for each strategy were created. The achieved results support that scenarios simulation, Rojo’s Model in particular, represents a valuable tool to plan the succession process in family businesses, since it enables the organization to answer quickly and more effectively to changes which may occur during the pathway.